The population dynamics of bank voles (Clethrionomys glareolus, Schreber 1780) and its significance for theory - Bujalska, Gabriela (Studia Ecologiae et Bioethicae, 2003)
This is an overview of long-term studies (1966-1997) on the bank vole - Clethrionomys glareolus (Photo 1). population inhabiting Crabapple Island in NE Poland. The history of recognition of causes affecting population dynamics as well as variable interpretation of the facts comprising the theory of functional relations in that population is described. Meandering ideas can be illustrated by Fig. 1. The population dynamics (each year data on population numbers in April, July, and October are shown) is presented in Fig. 2. The evidence is provided that the population exhibits a weak 3.8 year and a much more clear 9.4-year cycle (Fig. 3). The number of sexually mature females, that is those able to reproduce, has been relatively stable and independent of the population size or of the immature female numbers (Fig. 4). The reason is the territoriality of mature females: the female territory (part of the female home range) cannot be visited by other mature females. A tendency toward territoriality was also noted among mature males, which numbers were limited by the availability of mature females, and therefore also relatively stable. Such a social system can be considered gynocentric.